Effectiveness of Green Synthesized ZnO Nanoparticles Against MDR Resistant Klebsiella Pneumoniae Isolated From Diabetic Foot on Some Virulence Factors Genes Expression: Efektivitas Nanopartikel ZnO Hasil Sintesis Hijau Terhadap Klebsiella pneumoniae Resisten MDR yang Diisolasi dari Kaki Diabetes pada Beberapa Ekspresi Gen Faktor Virulensi - Al-Mousawi, HaiderTurky Mousa; Jadooa, Mustafa Muhammed; Al-bderee, Nadhim Mushtaq (Indonesian Journal on Health Science and Medicine, 2024)
Diabetic foot ulcers are a major public health problem and are quite costly for diabetic patients. Besides, patients with diabetic foot ulcers often have a poor quality of life. Most of the main complications of diabetic foot ulcers are the bacterial infection that leads to gangrene when different types of antibiotics fail to prevent bacterial infections. The research proposed in this study aims to determine the most effective synthesis type of Zinc oxide nanoparticles (ZnO NPs) and study its effect on some virulence factor genes expressions. Research includes the isolation and identification of several bacterial species by biochemical tests, as well as confirmation by the Vitek system and molecular diagnostics. Out of 100 swabs, 26 samples were found to be contaminated with bacteria Klebsiella pneumoniae is one the main virulence factor that develops of diabetic foot ulcers. The biological production of Zinc Oxide was using bacteria Pseudomonas aeruginosa. The characterization of the Zinc Oxide products was using the Ultra-violet Visible spectrophotometer, Fourier transform infrared spectroscopy, Scanning electron microscopy, X-Ray diffraction spectrum very small crystals with a large spherical shape were formed, with a size of 13.5 nm. The genes were included as the bacterial virulence factors coding genes, MagA of gene Klebsiella pneumoniae, which are responsible for the production of exotoxins that cause sepsis, necrosis, tissue necrosis and non-healing. The expression of MagA genes the different before and after treatment with ZnO NPs. The mRNA for both genes was extracted alongside the mRNA for 16SrRNA acting as housekeeping gene. All mRNAs were converted to cDNA through RT-PCR technique and then measure the expression by qPCR. The expressions of MagA genes for the biological product nanomaterial, bacterial nanomaterial, were significant for all the isolates with P<0.01. In conclusion from the foregoing the biological nanoparticles product was more sufficient for inhibition of most isolates. Highlights: Diabetic foot ulcers worsen by bacterial infections, causing severe complications. ZnO nanoparticles synthesized biologically; bacterial virulence gene expression analyzed. ZnO nanoparticles significantly inhibited K. pneumoniae virulence with P<0.01. Keywords: K. pneumoniae, P. aeruginosa, ZnO NPs, Mucoviscosity associated a gene (MagA) and gene expression